2014
DOI: 10.1074/jbc.m113.530576
|View full text |Cite
|
Sign up to set email alerts
|

A SnapShot of Ubiquitin Chain Elongation

Abstract: Background: Polyubiquitin chains are signaling polypeptides altering the fate of substrates. Results: A Lys-48-ubiquitin chain of a length greater than four, but not its Lys-63 linkage counterparts, slowed the rate of additional ubiquitin conjugation. Conclusion:The ubiquitin chain length and linkage may impact kinetic rates of chain elongation. Significance: Our findings suggest a self-restraining mechanism that limits Lys-48-polyubiquitination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…For example, in the case of K48-linked polyubiquitin, a length of four is generally considered optimal for molecular recognition of the 26 S proteasome ( 12 ), while the nuclear protein localization protein 4 is selective for K48-linked chains longer than six ( 13 ). It was reported that K48-linked tetraubiquitin (Ub 4 ) slows down further ubiquitination ( 14 16 ), while this is not the case for K63-linked Ub 4 ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the case of K48-linked polyubiquitin, a length of four is generally considered optimal for molecular recognition of the 26 S proteasome ( 12 ), while the nuclear protein localization protein 4 is selective for K48-linked chains longer than six ( 13 ). It was reported that K48-linked tetraubiquitin (Ub 4 ) slows down further ubiquitination ( 14 16 ), while this is not the case for K63-linked Ub 4 ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, SCF βTrCP /IκBα (EE)–Ub (I647) and Cdc34∼Ub (K48R/I555), preassembled in separate tubes, were each treated with apyrase to deplete ATP prior to mixing for ubiquitination. The effectiveness of ATP depletion by the apyrase protocol was validated previously ( 24 ). The results revealed that FRET plateaued at 30 min, utilizing about 20% of substrate input ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm this effect, we have performed competition experiments with the phospho-β catenin degron peptide as a competitor. Previous crystallographic and biochemical studies have shown binding of the phospho-β catenin degron peptide to βTrCP ( 21 ) and ability of this peptide to support ubiquitination by SCF βTrCP ( 24 ). As shown, the phospho-β catenin degron peptide was able to effectively compete against the fluorescent IκBα substrate by blocking the FRET IκBα diubiquitination ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous measurements of ubiquitination rates relied on quantification of protein bands from Western blots (e.g. [21][22][23][24]). While reliable, SDS-PAGE and antibody detection steps are time-consuming and expensive.…”
Section: Introductionmentioning
confidence: 99%